Problems and methods of assessing the level of digital development of construction participants in a multiproject environment - Dubinin, D.V. (Ways to Improve Construction Efficiency, 2023)
Since the beginning of the war, the construction industry, along with the entire system of functioning of the country’s economy, is undergoing significant transformations caused by military actions, structural changes, and digital technologies. Assessing the level of digital development of construction participants in a multi-project environment is a multifaceted and complex task, part of which is solved in the article. The main challenge of a multi-project environment is the diversity of construction projects, each with its own stakeholders, requirements and digital ecosystems. This diversity often leads to differences in digital development among participants, which hinders collaboration, efficiency, and project outcomes. Understanding and addressing these challenges is essential to foster alignment, integration and digital innovation across the construction ecosystem.Challenges in assessing digital development include interoperability issues, cultural resistance to change, and the lack of standardized assessment metrics. Interoperability problems arise due to the use of different software platforms and data formats, which prevents seamless collaboration and data exchange between construction participants. Cultural resistance to change, common in traditional construction practices, creates obstacles to the adoption of digital technologies and the introduction of new work processes. In addition, the lack of standardized indicators and evaluation systems makes it difficult to compare the digital maturity of projects and organizations.By addressing these challenges and using appropriate methodologies, construction stakeholders can navigate the complexities of digital development in a multi-project environment, encouraging efficiency, innovation and collaboration in the construction ecosystem. Digitization is essential to meet the growing demands of modern construction projects and achieve sustainable success in the digital age.